2021
DOI: 10.7554/elife.54894
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of nodal morphogen signaling is shaped by co-receptor expression

Abstract: Embryos must communicate instructions to their constituent cells over long distances. These instructions are often encoded in the concentration of signals called morphogens. In the textbook view, morphogen molecules diffuse from a localized source to form a concentration gradient, and target cells adopt fates by measuring the local morphogen concentration. However, natural patterning systems often incorporate numerous co-factors and extensive signaling feedback, suggesting that embryos require additional mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 95 publications
4
22
0
Order By: Relevance
“…Nodals are well known to bind to the EGF-CFC co-receptor Oep 36 , 66 , which is essential for Nodal signaling 67 . Furthermore, the signaling range and distribution of Squint was shown to be extended in the absence of oep 40 , 41 , but a direct effect of Oep on Nodal dispersal at the nanometer-to-micrometer scale has not yet been directly demonstrated. To test whether immobile Squint in our experiments was due to binding to Oep, we co-injected 0.3 pg, 3 pg and 30 pg of Oep-encoding mRNA together with the Squint-HaloTag construct and compared the diffusion properties of Squint in conditions of oep overexpression with those of endogenous Oep levels.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nodals are well known to bind to the EGF-CFC co-receptor Oep 36 , 66 , which is essential for Nodal signaling 67 . Furthermore, the signaling range and distribution of Squint was shown to be extended in the absence of oep 40 , 41 , but a direct effect of Oep on Nodal dispersal at the nanometer-to-micrometer scale has not yet been directly demonstrated. To test whether immobile Squint in our experiments was due to binding to Oep, we co-injected 0.3 pg, 3 pg and 30 pg of Oep-encoding mRNA together with the Squint-HaloTag construct and compared the diffusion properties of Squint in conditions of oep overexpression with those of endogenous Oep levels.…”
Section: Resultsmentioning
confidence: 98%
“…Second, effective diffusion coefficients on a tissue level across a cube of approximately 8 × 8 × 8 cells measured by fluorescence recovery after photobleaching (FRAP) were found to be much lower for Nodals than for Leftys (Cyclops < Squint < Lefty1 < Lefty2) 25 , 37 39 . Third, it has been shown that Nodals bind their receptors with nanomolar affinity 14 , and manipulating the levels of the co-receptor Oep modulated the Nodal signaling range and distribution 40 , 41 . However, it remains unclear whether and how such treatments affect Nodal and Lefty movement, how effective diffusivity through a tissue emerges from interactions at the molecular scale, how binding on the cell surface contributes to Nodal and Lefty movement, and how tissue geometry affects morphogen spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Zebrafish suggest that the range of Nodal signaling is limited through its capture by the coreceptor Cripto 38 . Although embryos deficient for Cripto cannot signal, Nodal protein from the margin can disperse over a much wider range than in wildtype embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Case for Nodal signalling is more complicated: although both activators and repressors of Nodal signalling locally diffuse at similar speeds [ 44 ], diffusion of activators but not repressors are significantly hindered in long range [ 56 ]. Recent work in zebrafish points to Nodal co-receptor One-eyed-pinhead (Oep) [ 87 ] for this hindrance [ 88 ]. Nodal gradients are robustly established owing repressive feedback from faster diffusing Lefty inhibitors in a Turing-type reaction–diffusion setting [ 56 ].…”
Section: Control Of a Morphogen Gradient's Diffusive Spanmentioning
confidence: 99%
“…Nodal gradients are robustly established owing repressive feedback from faster diffusing Lefty inhibitors in a Turing-type reaction–diffusion setting [ 56 ]. Interestingly, both mutants lacking Lefty inhibitors [ 89 ] and ligand trapping Oep co-receptor [ 88 ] result in pervasive Nodal signalling with expanded gradients and lethal phenotypes. Evidently, what sets up the final reach of a morphogen field depends on the regulation of long-range diffusivity and signalling of ligands [ 90 ].…”
Section: Control Of a Morphogen Gradient's Diffusive Spanmentioning
confidence: 99%